Objetos transplantados: a presença da mobília na arte - Roberto Bethonico de Figueiredo (2015)
The presence of furniture in the arts is a study of the furniture belonging to our daily lives that have been transformed into works of art. The artists usurped the usefulness of these furnishings throwing them on grounds that remain in constant oscillation, which brought up a plurality of concepts resulting from this ambiguity: sometimes we perceive them as furniture only, then no more. In order to shelter the research field that involves the furnishings/works, the study was structured and presented in the form of a Museum, the Instituto da Mobília na Arte I.M.A. The research was divided into rooms where issues relating to the functioning of the Institute are approached: collection of photographic reproductions, curatorship, critical essay, exhibition and personal artistic production. As a cutting of its object of study, the Instituto da Mobília na Arte presents part of its collection in the exhibition Strange Presence: the furniture in contemporary Brazilian art an unlike similar.